Analisis Pengadaan Bahan Baku di PT. Kohwa Precision Indonesia Menggunakan Metode Triple Exponential Smoothing - Anna Dara Andriana; Syukron Alawy (Majalah Ilmiah UNIKOM, 2022)
PT. Kohwa Precision Indonesia is a company that produces spare parts for two-wheeled and four-wheeled motor vehicles. PT.Kohwa Precision Indonesia produces products using a make-to-order method, which means that production will be executed when there is an order. As for the procurement process, the company conducts procurement once a month. With a procurement process that provides raw material inventory, the procurement department, namely Product Planning Control (PPC) finds it difficult to determine how much raw material for making spare parts must be procured to meet the needs in the production process for the next period. The risk that occurs if too many raw materials are purchased will result in damage to raw materials due to the length of storage, while if there are too few raw materials for making spare parts, it can result in the production process running outside of the intended plan. Forecasting is the right way to deal with uncertainty, so in this study using a method based on time series sales of spare parts with seasonal fluctuating data patterns will use the triple exponential smoothing forecasting method. The purpose of this study is to assist the PPC department in determining the amount of raw materials that must be procured by the PPC department, so that it is hoped that there will be no excess or shortage of raw materials during the procurement period. This research resulted in the number of raw materials that must be procured by the PPC section for example STKM11A 38.0 x 60.5 FM raw materials as many as 132.183 pcs, so that the PCC division no longer finds it difficult to determine the amount of procurement of each raw material. Key Words : procurement, triple exponential smoothing, forecasting